Study on Rectifier Technology in Forebay of Pumping Station - SU Zhengyang; LU Jiawei; ZHANG Zhitao; LI Hanzhang; SU Zhengzhong (Renmin Zhujiang)
Design of urban drainage pumping stations is susceptible to land area, water pipe networklayout, surrounding terrain conditions and construction requirements.It is often difficult to meetthe requirements of favourable hydraulic conditions in the design specifications of generalpumping stations. This paper analyzes the inflow characteristics of the forebay of urban pumpingstation, summarizes and classifies the existing rectifier technology of the pumping station intofive types such as diversion pier rectifier technology, diversion grid rectifier technology,bottom sill rectifier technology, pressure plate rectifier technology and water distribution holerectifier technology, and introduces the engineering application status of each technology, andthe advantages, disadvantages and applicable scope of each technology in detail, which can providereference for improving the reliability of urban pumping station system.